Strengthening Social Studies Teachers’ Competence in Developing Digital Storybooks Based on Dayak Deah Local Wisdom - Dewicca Fatma Nadilla; Herry Porda Nugroho Putro; Wisnu Subroto; Ilham Galih Pambudi (Borneo Research and Education Center, 2026)
This community service activity aimed to strengthen teachers’ understanding in developing digital teaching materials through storybook digital based on Dayak Deah local wisdom for social studies learning at SMPN 2 Upau, Tabalong Regency. The activity was carried out through workshop, mentoring, and classroom implementation stages involving 12 teachers, including social studies teachers as the main participants. Data collection was conducted using pretest-post test instruments, observation, interviews, and student response questionnaires. The workshop focused on introducing digital teaching materials, training in developing storybook digital using Canva, and integrating Dayak Deah cultural values into social studies learning materials. The results showed that teachers’ average score increased from 62 points in the pretest to 72 points in the posttest after participating in the training and mentoring activities. The improvement was mainly seen in teachers’ understanding of Canva operation, storybook preparation, integration of local cultural values, and visual design of digital teaching materials. The classroom implementation results also showed positive student responses, with an average score of 87.33% categorized as very feasible. Students considered the storybook digital easy to use, attractive, and helpful in understanding social studies materials and local cultural values. The activity indicates that integrating digital technology and local wisdom can support more contextual and meaningful social studies learning while helping preserve local cultural values in educational practices.